ChemInform Abstract: Directed C—H Alkenylation of Quinoline N‐Oxides at the C‐8 Position Using a Cationic Rhodium(I) Catalyst. Issue 39 (23rd September 2014) - Shibata, Takanori; Matsuo, Yusuke
Abstract A novel method using a N‐oxide directing group is developed for the regioselective C‐8‐alkenylation of quinoline N‐oxides with diarylacetylenes to give predominantly E‐products.